2003
DOI: 10.1046/j.1526-0968.2003.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Based Adsorbers for Therapeutic Immunoadsorption

Abstract: Peptides as ligands for immunoadsorption exhibit several potential advantages over native proteins. Two newly developed adsorbers are based on peptides covalently coupled to sepharose CL-4B. Globaffin is capable of binding immunoglobulins independent from their antigen specificity and thus, applicable in transplant recipients and several antibody mediated autoimmune diseases. Among others, the most important disorders suitable for the treatment with Globaffin are rheumatoid arthritis, systemic lupus erythemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 38 publications
0
41
0
7
Order By: Relevance
“…The peptide matrix of Globaffin binds to IgG and circulating immune complexes with high affinity and with lower affinity to IgA and IgM. Its binding characteristics are comparable to protein A Sepharose [20]. Compared to adsorbers based on bacterial components such as protein A, synthetic peptide ligands do not harbor potential infection risks.…”
Section: Discussionmentioning
confidence: 99%
“…The peptide matrix of Globaffin binds to IgG and circulating immune complexes with high affinity and with lower affinity to IgA and IgM. Its binding characteristics are comparable to protein A Sepharose [20]. Compared to adsorbers based on bacterial components such as protein A, synthetic peptide ligands do not harbor potential infection risks.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, specific epitopes can be defined for the corresponding pathogenetic autoantibodies, and such epitopes can be used as a lead structure for the development of a specific peptide ligand in an immunoadsorption device that avoids the temporary humoral immunosuppression caused by the removal of immunoglobulin. Rönspeck et al [67] recently described a new generation of adsorbents for autoantibody elimination based on synthetic peptides and their use in immunoadsorption therapy for specific removal of ␤ 1 -adrenergic autoantibodies in idiopathic dilated cardiomyopathy. Andersen et al [68] recently described a similar approach using synthesized ganglioside epitopes for oligosaccharide-specific immunoadsorption therapy for Guillain-Barre syndrome.…”
Section: New Concepts In Immunoadsorptionmentioning
confidence: 99%
“…More recently developed adsorber systems contain synthetic peptides covalently bound to a sepharose matrix as ligands for human Ig. Fresenius Medical Care provides two peptide-based adsorber systems, the Globaffin adsorber contains a peptide (PGAM146) which unspecifically binds to IgG, CIC and to a lesser extend to IgA and IgM [29].…”
Section: Adsorber Systemsmentioning
confidence: 99%
“…The Coraffin adsorber has been developed based on peptide epitopes recognized by anti-b1 (Table III) Myasthenia gravis Guillain-Barre-syndrome Life-threatening systemic vasculitis adrenergic receptor autoantibodies (b 1 -AAB) in patients suffering from idiopathic dilatative cardiomyopathy (DCM), thus specifically removing antigen specific autoantibodies from patients' plasma. Coraffin contains two different peptide ligands, PDCM349 related to the extracellular loop 1 of the b1 adrenergic receptor and PDCM075 related to the extracellular loop 2 [29]. A pilot trial by Wallukat et al demonstrated the successful application of a prototype of Coraffin in DCM patients [30].…”
Section: Adsorber Systemsmentioning
confidence: 99%